What Drives Personal Consumption? The Role of Housing and Financial Wealth - Jiri Slacalek (European Central Bank (ECB), 2009)
I investigate the effect of wealth on consumption in a new dataset with financial and housing wealth from 16 countries. The baseline estimation method based on the sluggishness of consumption growth implies that the eventual (long-run) marginal propensity to consume out of total wealth is 5 cents (averaged across countries). While the wealth effects are quite strong—between 4 and 6 cents—in countries with more developed mortgage markets and in market-based, Anglo-Saxon and non euro area economies, consumption only barely reacts to wealth elsewhere. The effect of housing wealth is somewhat smaller than that of financial wealth for most countries, but not for the US and the UK. The housing wealth effect has risen substantially after 1988 as it has become easier to borrow against housing wealth.
Keywords: E21; E32; C22; 330; Consumption Dynamics; housing prices; Portfolio Choice; wealth effect; Immobilienpreis; Privater Konsum; Kapitalanlage; Vermögenseffekt; Privater Konsum; OECD-Staaten